A history of Herat - Mahendrarajah, Shivan. (Edinburgh)
xiv, 379 sayfa
Keywords: “This book tells the history of Herat, from its desolation under Chingiz Khan in 1222, to its capitulation to Tamerlane in 1381. Unlike the other three quarters of Khurasan (Balkh, Marw, Nishapur), which were ravaged by the Mongols, Herat became an important political, cultural and economic centre of the eastern Islamic world. The post-Mongol age in which an autochthonous Tajik dynasty, the Kartids, ruled the region set the foundations for Herat's Timurid-era splendors.Divided into two parts (a political-military history and a social-economic history), the book explains why the Mongol Empire rebuilt Herat: its rationales and approaches; and Chinggisid internecine conflicts that impacted on Herat's people. It analyses the roles of Iranians, Turks and Mongols in regional politics; in devising fortifications; in restoring commercial and cultural edifices; and in resuscitating economic and cultural activities in the Herat Quarter.” --